(untitled) (Current Problems in Rail Vehicles, 2021)
The aerodynamics in railway application is a typical example of the topic that occurs on the interface between vehicles and infrastructure while both systems affect each other. The magnitude of effects is also determined by surrounding environment that represents atmospheric conditions or specific operational situations. During the analysis of aerodynamic effects, it requires a definition of reference conditions or scenarios to which the results are referred and in which context they are further compared or assessed. In experiment it is important to correct or transform measured data into this reference state. The article briefly describes examples of reference vehicles and infrastructure that are used in the assessment of aerodynamic effects on open track or in tunnel. There are shown reference scenarios relating to some aerodynamic topics, there is emphasized on specific questions in their application and shown examples of boundary conditions influence on the magnitude of some effects.